Comparative mitogenome analysis and phylogenetic inference of the genus Ultragryllacris (Orthoptera: Gryllacrididae) - Lu, Xiangyi; Luo, Haiyu; Zhang, Qianwen; Bian, Xun (Zootaxa, 2023)
The genus Ultragryllacris is mainly distributed in China and Thailand, and the type species Ultragryllacris pulchra Gorochov & Dawwrueng, 2015 includes four subspecies. Up to now, these subspecies were identified mainly based on their morphological characteristics, and no study on the molecular identification of subspecies and phylogenetic analyses has been reported. Here we obtained three mitogenomes of U. pulchra rubricapitis and one mitogenome of Homogryllacris yunnana and reconstructed the relationship of Ultragryllacris among genera. Species identification was performed with ABGD, jMOTU, and NJ tree based on cox1 (658 bp) and cob (550 bp) genes. The mitogenomes of U. pulchra rubricapitis and H. yunnana were 15558–16625 bp and 16209 bp in length, respectively. Most of the PCGs started with the typical ATN codons and terminated with complete TAA/TAG. Four mitogenomes showed positive AT skews and negative GC skews. Besides, the phylogenetic tree of BI and ML revealed that Ultragryllacris was a monophyletic group. One geographical population of Ultragryllacris pulchra rubricapitis was described and illustrated.